2013
DOI: 10.1155/2013/130570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transverse Baffle Design on Reducing Liquid Sloshing in Partially Filled Tank Vehicles

Abstract: Longitudinal liquid sloshing in partially filled clear-bore tanks causes extensive degradation of tankers braking performance. To reduce the negative effect of longitudinal liquid sloshing on tankers, three kinds of transverse baffles were designed, namely, the conventional baffle, the circular baffle, and the staggered baffle. Each kind of baffle took several forms to investigate the impact of baffle installation angle, the sizes of holes pierced on the baffle, and their arrangement on the antisloshing effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…The equivalent mechanical models have been shown to be effective and simple to describe liquid sloshing. 16 In this section, the numerical solution of the liquid sloshing in lateral and longitudinal directions is solved based on approximate algorithms for the horizontal cylinder tank. It is assumed that baffles are not considered in the tank.…”
Section: Improved Equivalent Model Of Liquid Sloshing For a Horizonta...mentioning
confidence: 99%
“…The equivalent mechanical models have been shown to be effective and simple to describe liquid sloshing. 16 In this section, the numerical solution of the liquid sloshing in lateral and longitudinal directions is solved based on approximate algorithms for the horizontal cylinder tank. It is assumed that baffles are not considered in the tank.…”
Section: Improved Equivalent Model Of Liquid Sloshing For a Horizonta...mentioning
confidence: 99%
“…Therefore, the first sloshing modal is the most important one. More details about the dynamics of liquid sloshing in partially filled tanks without or with baffles can be found in Zheng et al [37][38][39] Equivalent mechanical model for liquid sloshing Dynamic analysis of liquid sloshing in partially filled tanks showed that liquid sloshing approximates to linear oscillation when external excitation is quite small. Besides, the modal analysis of liquid sloshing reveals that the first modal is the most important one to reflect the dynamics of liquid sloshing.…”
Section: Dynamic Analysis Of Liquid Sloshing In Partially Filled Tanksmentioning
confidence: 99%
“…Among them, nonlinearity, linear theory, and simulation analysis of liquid sloshing were deeply studied. 1,2 In many fields, liquid sloshing brings a series of problems, such as driving instability, [3][4][5][6] sloshing noise, 7 structural damage, and evaporative emission. 8 Therefore, the effective control of liquid sloshing is a research direction that scholars pay close attention to at present.…”
Section: Introductionmentioning
confidence: 99%